IMPLEMENTASI PENYEDIAAN INFORMASI KEPARIWISATAAN DI KABUPATEN TANGGAMUS PERSPEKTIF SIYASAH TANFIDZIYAH - Indy Annisa; Nurnazli Nurnazli; Li'izza Diana Manzil (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study discusses the implementation of the provision of tourism information in Tanggamus Regency based on Article 7 paragraph (1) letter (a) of Tanggamus Regency Regional Regulation Number 6 of 2019 concerning Integrated Tourism Development from a siyasah tanfidziyah perspective. This study is motivated by the still suboptimal provision of tourism information, especially regarding the security and safety of tourists in several tourist destinations in Tanggamus Regency. The type of research used is field research with a qualitative descriptive approach. Data were obtained through interviews, documentation, and literature studies. The results of the study indicate that the Tanggamus Regency Government through the Tourism Office has made various efforts to provide tourism information through social media, tourism promotions, providing appeals, and providing information boards at several tourist locations. However, the implementation is still not optimal due to limited information facilities, less than optimal management of digital information media, minimal signs and safety warning signs, and limited human resources. From a siyasah tanfidziyah perspective, the implementation of this policy does not fully reflect the implementation of the government's mandate optimally because the government has an obligation to provide protection, security, and comfort to the community and tourists.